Optimization with levosimendan improves outcomes after left ventricular assist device implantation. (1st June 2019) - Kocabeyoglu, Sinan Sabit; Kervan, Umit; Sert, Dogan Emre; Karahan, Mehmet; Aygun, Emre; Beyazal, Osman Fehmi; Unal, Ertekin Utku; Akin, Yesim; Demirkan, Burcu; Pac, Mustafa
Abstract: OBJECTIVES: The aim of this study was to examine the haemodynamic effects of preoperative levosimendan infusion in patients who underwent left ventricular assist device implantation and evaluate the prognoses. METHODS: Between May 2013 and October 2018, 85 adult patients who underwent left ventricular assist device implantation were included; 44 and 41 patients suffered from dilated cardiomyopathy and ischaemic cardiomyopathy, respectively. Patients were divided into 2 groups: group A (58 patients) included those who received levosimendan infusion in addition to other inotropes and group B (27 patients) included those who received inotropic agents other than levosimendan. Levosimendan infusion was started at a dose of 0.1 µg⋅kg −1 ⋅min −1 for a maximum of 48 h without a bolus. The primary outcome was early right ventricular failure (RVF). The secondary outcomes were in-hospital mortality, need for right ventricular assist device, late RVF and recovery of end-organ functions. The safety end points of levosimendan included hypotension, atrial fibrillation, ventricular tachycardia or fibrillation and resuscitated cardiac arrest. RESULTS: Patient characteristics were similar in both groups. No significant differences between groups were observed in the rates of early mortality, RVF, need for right ventricular assist device, cardiopulmonary bypass time and intensive care unit stay. Survival rates at 30 days, 1 year and 3 years and freedom from late RVF were similar between the groups. Administration of levosimendan was safe, generally well-tolerated and not interrupted because of side effects. CONCLUSIONS: Levosimendan therapy was well-tolerated in patients who received permanent left ventricular assist devices. Combined preoperative therapy with inotropes and levosimendan significantly improves end-organ functions.